An Updated Assessment of Personal Protective Order Statutes in the United States: Have Statutes Become More Progressive in the Past Decade?. (May 2018) - Richards, Tara N.; Tudor, Alison; Gover, Angela R.
The Personal Protection Order (PPO) is one civil intervention all states provide to victims of domestic violence; however, each state varies widely in who can access PPOs, what protections are included in PPOs, and how they are enforced. Given the many changes to state PPO statutes over the last decade, this research replicates and updates DeJong and Burgess-Proctor's research on PPOs' victim-friendliness (using states' 2003 PPO statutes) by examining states' 2014 PPO statutes. Findings suggest that states have become more victim-friendly with most states ranking in the highest category of victim-friendliness. Implications for policy and practice are discussed.